2023
DOI: 10.3390/polym15030692
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Manufacturing of Functional Paper with Modified by N-Methylmorpholine-N-oxide Surfaces

Abstract: The manufacturing of paper with new functional properties is a current problem today. A method of modifying the surface layer of paper by the partial dissolution of cellulose on its surface is proposed. N-Methylmorpholine-N-oxide (NMMO) is proposed for use as a solvent, the regeneration of which provides an environmentally friendly process. It was shown that among the possible hydrate forms of the solvent, the monohydrate and higher-melting forms are optimal for modifying the paper surface. The temperature–tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…)-based films [72][73][74][75]. Recently, Makarov et al reported N-methylmorpholine-N-oxide (NMMO) surface treatment based on the partial dissolution of cellulose and its coagulation for modification of a paper surface [30]. In general, surface-modified RC films exhibit uniform surface morphology as well as high transmittance compared with surface-modified papers, probably due to a perfect dissolution and regeneration process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…)-based films [72][73][74][75]. Recently, Makarov et al reported N-methylmorpholine-N-oxide (NMMO) surface treatment based on the partial dissolution of cellulose and its coagulation for modification of a paper surface [30]. In general, surface-modified RC films exhibit uniform surface morphology as well as high transmittance compared with surface-modified papers, probably due to a perfect dissolution and regeneration process.…”
Section: Resultsmentioning
confidence: 99%
“…Various surface modification techniques based on chemical agents and fluorinated coating materials have been developed to control the wetting properties of cellulose films because of their low surface energy [28,29]. Recently, Makarov et al reported a facile method to modify the surface layer of cellulose paper with a N-methylmorpholine-N-oxide (NMMO) solvent [30]. Deep interactions between NMMO and cellulose fiber can lead to the strong swelling and dissolution of cellulose, leading to a decrease in air permeability and water absorption.…”
Section: Introductionmentioning
confidence: 99%